2015
DOI: 10.1016/j.brainres.2015.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Limits of ideomotor action–outcome acquisition

Abstract: Ideomotor theory proposes that goal-directed action emerges from the implicit, incidental acquisition of bi-directional associations between actions and their outcomes. In line with this idea, a simple two-stage priming paradigm has provided evidence that presentation of outcomes primes previously associated actions. In the current study we compare the standard priming paradigm with two actions and two unique outcomes (Experiment 1) with two more complex, but otherwise identical versions (Experiment 2: two vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Previous studies have shown that actors performing spatial responses tend to code their actions in terms of salient visual Yamaguchi & Proctor, 2011) or Action Goal Sharing 8 auditory (Elsner & Hommel, 2001) events that these actions generate, such as responsecontingent signals on a screen or auditory events, at least if the action effects are sufficiently salient (Dutzi & Hommel, 2009) and the task is not too complex (Watson, van Steenbergen, de Wit, Wiers & Hommel, 2015). In the present study, we used visual action effects that were triggered by pressing the response keys (see Figure 1).…”
Section: The Present Studymentioning
confidence: 99%
“…Previous studies have shown that actors performing spatial responses tend to code their actions in terms of salient visual Yamaguchi & Proctor, 2011) or Action Goal Sharing 8 auditory (Elsner & Hommel, 2001) events that these actions generate, such as responsecontingent signals on a screen or auditory events, at least if the action effects are sufficiently salient (Dutzi & Hommel, 2009) and the task is not too complex (Watson, van Steenbergen, de Wit, Wiers & Hommel, 2015). In the present study, we used visual action effects that were triggered by pressing the response keys (see Figure 1).…”
Section: The Present Studymentioning
confidence: 99%
“…The more a task stresses the induced actioneffect associations and the more they contribute to a good performance in the task, the more likely participants are going to use these associations. In this sense, in addition to the design of the acquisition phase (Herwig et al 2007), the complexity of the task (Watson et al 2015) and other factors, the task relevance of effect tones and the presentation of postresponse effects are two more factors to affect whether the induced action-effect associations are used for action control.…”
Section: Resultsmentioning
confidence: 99%
“…Ideomotor learning and effect-based action control are two well-studied factors in human action control (Hommel et al 2016). In principle, they are suitable for psychological studies for they are believed to take place incidentally, implicitly and automatically (Watson et al 2015). However, beyond the experimentally induced action-effects, experimentindependent action-effects, for instance body-related actioneffects, are still sufficient for ideomotor action control (Pfister 2019).…”
Section: Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations